The Mollusks of the Duck River Drainage in Central Tennessee - Henry Van der Schalie (Hello World!, 1973)
Relatively few papers have been written on the mollusks of the Tennessee River drainage. The most important are those of A. E. Ortmann (1912, 1913, 1918, 1920, 1921, 1924a, 1924b, and 1925). Ortmann, collaborating with Bryant Walker, essentially developed the basic classification for the Naiades, or freshwater mussels. They were also sufficiently versed in the ecology and distribution of mussels to provide broad and significant outlines of zoogeographic relationships. With the meager gear then at their disposal, the best and only method to survey smaller streams was by handpicking; for large river as the Tennessee itself (except in such shallow areas as 'Muscle Shoals') larger boats and clammer's gear were need- ed.Walker often identified mussels for those making surveys for the U. S. Bureau of Fisheries when intensive work was done in connection with the cluming industry and he was thus able to obtain valuable locality records. In that heyday of colecting, scuba diving had not come into use and, consequently, it was necessary to work at low water stages so that most of those early surveys were accomplished in late summer or fall. Even with modern gear low water stages are best for collecting.